PENGARUH PEMBERIAN REWARD TERHADAP HASIL BELAJAR PADA MATA PELAJARAN MATEMATIKA KELAS V SDN 094097 SIMPANG PONGKALAN TONGAH KABUPATEN SIMALUNGUN - Priskila Rosdiana Sipayung; Regina Sipayung; Dyan Wulansari Hutahaean; Darinda Sofia Tanjung (Universitas Negeri Medan, 2021)
This study aims to determine the effect of giving rewards on learning outcomes in fifth grade mathematics subjects at SDN 094097 Simpang Pongkalan Tongah. The research method used is an experimental method with quantitative research. To obtain the necessary data in the form of a test with a total of 40 questions. The research at SDN 094097 Simpang Pongkalan Tongah in class V was carried out from 10 to 11 May 2021. The number of research samples was 16 students based on the saturated sample technique. The results of statistical calculations show that the ability of students in answering post-test questions with the reward method is included in the very good category with an average value of 84.06 in the very good category. Meanwhile, the students' ability to answer the post-test questions with the demonstration method was included in the good category with an average value of 70.31 in the good category. This study used the normality test with the results of 0.200> 0.05. Then the homogeneity test with a significance value of 0.344 > 0.05. Furthermore, hypothesis testing is to compare the value of tcount with ttable. Obtained the value of tcount = 4.111 while ttable = 1.746. Because tcount > ttable (4.111 > 1.746) then Ha is accepted and Ho is rejected. Through the t test, it can be concluded that there is a significant effect between giving rewards to learning outcomes.Keywords: Giving Rewards, Mathematics, Learning Outcomes